Prevalence of psychiatric disorders among the adult population in a rural community of Jammu, India: a cross-sectional study - Bailam, Sandeepa; Sudershan, Amrit; Sheetal; Younis, Mohd; Arora, Manu; Kumar, Hardeep; Kumar, Parvinder; Kumar, Dinesh (Frontiers in Psychiatry, 2024)
Background: Mental health is crucial for overall well-being, but rural areas often face difficulties in accessing mental health services and understanding psychiatric disorders. Aim:This study aimed to address these issues by assessing the prevalence of psychiatric disorders among adults in rural Jammu and examining how socio-cultural and demographic factors are related to these disorders. Methods: A sample of 1,016 adults from rural Jammu was surveyed using the Mini International Neuropsychiatric Interview (MINI). Data were collected through house-to-house visits conducted by trained investigators. Descriptive and inferential statistics, including frequency distribution and odds ratio, were employed to analyze the data respectively.Results: Overall, 20.67% of the participants had a psychiatric disorder. Alcohol dependence was the most common condition, affecting 12.30% of the individuals, followed by generalized anxiety disorder at 3.14%. The study found significant associations between psychiatric disorders and several factors. Specifically, older people were more likely to have psychiatric disorders, with an odds ratio of 3.7 [2.07-6.59]. Married individuals also had a higher likelihood of experiencing psychiatric disorders ). Those with less schooling were at an increased risk, with an odds ratio of 7. 77 [2.31-26.09], and people from lower socioeconomic backgrounds were more likely to have these disorders as well (OR: 5.1 [2.4-10.5]). Discussion & Conclusion: The findings underscore the complex association between socio-demographic factors and mental health outcomes in rural areas of Jammu region. Addressing these disparities requires targeted interventions and policies that account for the unique socio-cultural contexts of rural populations. By understanding the specific challenges faced by these communities, policymakers and healthcare providers can develop more effective strategies to enhance mental health services and promote well-being.